Ruh Menurut Ibn Qayyim Al-Jawziyyah dalam Perspektif Psikologi - Abdul Mujib (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
Throughout history, Ibn Qayyim al-Jawziyyah has been recognized as a Muslim intellectual figure who lived amidst the stagnation of thought, amidst the overwhelming scripturalism. Ibn Qayyim, however, unveiled this stagnation and scripturalism by unraveling the essence of human existence claimed by God Himself, namely the issue of the soul. Ibn Qayyim’s in-depth study of the soul is captured in his book titled Kitab al-Ruh. It is a document of knowledge that views the soul as a unique structure of human self compared to the body. This study examines Ibn Qayyim’s paradigm of the soul in its relevance to psychology. To what extent does Ibn Qayyim’s concept of the soul contribute to and intersect with the discourse of psychology.